Polyethylene-based heat-resistant shielding material and preparation method thereof
By using ultra-high molecular weight polyethylene (UHMWPE), crosslinking agent DTBP, additive TMPTMA, combined with lead (Pb) filler, heat-resistant shielding material is prepared, which solves the problem of insufficient heat resistance and radiation resistance of existing polymer matrix materials, and achieves the efficient shielding performance of the material in high temperature and high radiation environments.
Patent Information
- Application Number
- CN202310452255.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-24
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-04-24
AI Technical Summary
The melting point, heat resistance and radiation resistance of existing polymer matrix shielding materials are insufficient, which limits their application in high-radiation environments such as nuclear reactors.
Ultra-high molecular weight polyethylene (UHMWPE) is used as the matrix, di-tert-butyl peroxide (DTBP) and trimethylolpropane trimethacrylate (TMPTMA) are used as crosslinking agents and additives, and lead (Pb) is used as shielding fillers, and shielding materials with high heat resistance and radiation resistance are prepared by crosslinking and hot pressing.
The tensile strength, elongation of break, bending strength and radiation resistance of the material are significantly improved, and its stability and shielding effect in high temperature and high radiation environments are enhanced.
Smart Images

Figure CN116715910B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of radiation shielding materials, and in particular relates to a heat-resistant shielding material and a preparation method thereof. Background Art
[0002] Nuclear energy is a new type of energy, which has the advantages of environmental protection, economy and safety compared with traditional energy. Nuclear reactors are composed of nuclear fuel, coolant, moderator, reflector material, structural material and shielding material. The fuel in the nuclear reactor will produce a large amount of energy and radiation when nuclear fission reaction occurs. These radiations include x-rays, gamma rays and neutrons, which are very harmful to the performance of shielding materials and human health. Therefore, the shielding ability and radiation resistance of shielding materials are crucial.
[0003] The use environment of shielding materials is full of radiation and heat. In the process of gamma-photons and neutrons interacting with extranuclear electrons and nuclei respectively, shielding materials will also generate heat. Therefore, the high heat resistance, thermomechanical properties and radiation resistance of shielding materials ensure the safety and location of their use. That is, the higher the above performance, the closer the use location is to the core, and the greater the value it plays.
[0004] At present, the commonly used shielding materials are polymer matrix, metal matrix, concrete and ceramic matrix. These shielding materials have some advantages and disadvantages at the same time. For example, the introduction of metal matrix in shielding material makes it have excellent heat resistance, high toughness and radiation resistance, but the solid solubility is insufficient after adding inorganic fillers (such as boron). Concrete shielding material has the characteristics of low cost and adjustable composition, but the shielding performance is poor. Ceramic-based shielding materials have good stability, heat resistance and radiation resistance, but their poor processing performance caused by brittleness limits their application. Polymer matrix is used in nuclear shielding materials because of its good processability, low density and small size. However, its low melting point, heat resistance and radiation resistance limit its application. Therefore, it is crucial to improve the melting point, heat resistance and radiation resistance of polymer matrix shielding materials.
[0005] Ultra-high molecular weight polyethylene (UHMWPE) is a type of high-density polyethylene (HDPE) with excellent processing properties and excellent thermomechanical properties. At present, there are studies on the introduction of heavy metals (such as Pb, W, Fe), rare earth elements (such as Sm, Eu, Gd) and boron-containing compounds into HDPE to make the shielding material have excellent shielding properties. However, these studies have ignored the thermomechanical properties and radiation resistance of HDPE. The UHMWPE cross-linked network constructed by X-ray, gamma-ray and electron beam irradiation has high mechanical properties and thermal stability. However, the particle sources used in these methods are very expensive, which limits their application.
[0006] In order to overcome the above problems, it is of great significance to develop a low-cost and easy-to-operate method to prepare heat-resistant shielding materials. Summary of the invention
[0007] The object of the present invention is to provide a heat-resistant shielding material and a preparation method thereof.
[0008] The invention provides a heat-resistant shielding material, which is prepared from the following raw materials in parts by weight: 100 parts of high-density polyethylene, 0.1-3.0 parts of a cross-linking agent, 0.2-6.0 parts of a cross-linking auxiliary agent, and 20-200 parts of a shielding filler.
[0009] Furthermore, the high-density polyethylene is ultra-high molecular weight polyethylene.
[0010] Furthermore, the cross-linking agent is a peroxide cross-linking agent.
[0011] Furthermore, the peroxide cross-linking agent is di-tert-butyl peroxide.
[0012] Furthermore, the cross-linking auxiliary agent is trimethylolpropane trimethacrylate.
[0013] Furthermore, the shielding filler is lead.
[0014] Further, it is prepared from the following raw materials in parts by weight: 100 parts of high-density polyethylene, 0.2-1.2 parts of cross-linking agent, 0.4-2.4 parts of cross-linking aid, and 80 parts of shielding filler. Preferably, it is prepared from the following raw materials in parts by weight: 100 parts of high-density polyethylene, 0.8-1.2 parts of cross-linking agent, 1.6-2.4 parts of cross-linking aid, and 80 parts of shielding filler.
[0015] The present invention also provides a method for preparing the above heat-resistant shielding material, which comprises the following steps: plasticizing high-density polyethylene, adding shielding filler, crosslinking agent and crosslinking auxiliary agent, mixing evenly, and hot pressing to obtain the heat-resistant shielding material.
[0016] Furthermore, the plasticizing temperature is 150-170° C., and the time is 5-15 min; the hot pressing temperature is 200-220° C., the pressure is 5-15 MPa, and the time is 15-25 min.
[0017] The present invention also provides an application of the above heat-resistant shielding material in the preparation of nuclear reactor devices, nuclear power plant operating devices, radioactive material transportation devices, radiation devices and medical and sanitary products thereof.
[0018] The present invention uses ultra-high molecular weight polyethylene (UHMWPE) as a matrix, di-tert-butyl peroxide (DTBP) as a crosslinking agent, trimethylolpropane trimethacrylate (TMPTMA) as a crosslinking aid, and lead (Pb) as a shielding filler to develop a new multifunctional heat-resistant shielding material with gamma-ray shielding, neutron shielding, radiation resistance, and heat resistance. The new multifunctional heat-resistant shielding material has broad application prospects in the preparation of heat-resistant shielding materials in nuclear reactor devices, nuclear power plant operating devices, radioactive material transportation devices, radiation devices, and medical and health products.
[0019] Obviously, according to the above contents of the present invention, in accordance with common technical knowledge and customary means in the art, without departing from the above basic technical ideas of the present invention, other various forms of modification, replacement or change may be made.
[0020] The above contents of the present invention are further described in detail below through specific implementation methods in the form of embodiments. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above contents of the present invention belong to the scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 :Mechanical properties of DTBP cross-linked UHMWPE shielding materials at room temperature: (A) tensile properties; (B) bending properties; (C) impact properties.
[0022] Figure 2 : Mechanical properties of DTBP cross-linked UHMWPE shielding materials at high temperatures: (A, B) tensile properties and bending properties at 70℃; (C, D) tensile properties and bending properties at 90℃.
[0023] Figure 3 : Crosslinking degree and heat resistance of DTBP crosslinked UHMWPE shielding materials: (A) crosslinking degree, (B) DSC curve, (C) Vicat softening temperature, (D) heat deformation curve.
[0024] Figure 4 :Mechanical properties of DTBP cross-linked UHMWPE shielding material after 200KGy γ-ray irradiation.
[0025] Figure 5 :Mechanical properties of DTBP cross-linked UHMWPE shielding material after 400KGy γ-ray irradiation.
[0026] Figure 6 :Mechanical properties of DTBP cross-linked UHMWPE shielding material after 600Kgy dose of γ-ray irradiation.
[0027] Figure 7: Effect of DTBP cross-linked UHMWPE shielding material on γ-ray and neutron shielding performance with increasing thickness. DETAILED DESCRIPTION
[0028] The raw materials and equipment used in the present invention are all known products, which are obtained by purchasing commercially available products.
[0029] The model / grade of ultra-high molecular weight polyethylene (UHMWPE) is L3000.
[0030] Example 1: Preparation of DTBP cross-linked UHNMWPE shielding material
[0031] According to the raw material ratio shown in Table 1, a cross-linked UHMWPE shielding material was prepared using an internal mixer and a hot press. The specific operation was as follows: ultra-high molecular weight polyethylene (UHMWPE) and lead (Pb) powder were dried at 80°C in a vacuum for 12 hours. UHMWPE was plasticized at 160°C for 10 minutes, and then Pb powder was added and mixed evenly for 10 minutes, and then a cross-linking agent (DTBP) and a cross-linking aid trimethylolpropane trimethacrylate (TMPTMA) were added and mixed for 15 minutes to obtain UHMWPE shielding material. Then, it was stored at room temperature for 24 hours, and hot pressed at 210°C and 10MPa for 20 minutes to prepare various DTBP cross-linked UHNMWPE shielding materials: 0.2phr DTBP, 0.5phr DTBP, 0.8phr DTBP, and 1.2phr DTBP.
[0032] Table 1 Raw material ratio
[0033]
[0034] The following is the preparation method of the control sample.
[0035] Control Example 1: Preparation of a control shielding material without added crosslinking agent
[0036] The raw materials UHMWP and Pb powder were weighed according to the ratio shown in Table 1, and the control shielding material without adding a cross-linking agent was prepared by referring to the method of Example 1: 0 phr DTBP.
[0037] Control Example 2: Preparation of control shielding materials using DCP or BPDH as crosslinking agent
[0038] Referring to the method of Example 1, the cross-linking agent DTBP was replaced with diisopropylbenzene peroxide (DCP) or 2,5-di-tert-butylperoxide-2,5-dimethylhexane (BPDH). It was found that the cross-linking reaction of the material occurred rapidly during the mixing stage, resulting in that Pb could not be well dispersed, and hot pressing could not prepare the material, and only a pile of slag-like substance could be obtained.
[0039] The beneficial effects of the present invention are demonstrated by experimental examples below.
[0040] Experimental Example 1: Mechanical properties test of DTBP cross-linked UHMWPE shielding material at room temperature
[0041] 1. Experimental methods
[0042] Tensile strength and elongation at break were tested on a tensile testing machine with an operating speed of 100 mm / min and a sample size of 180 × 10 × 4 mm. The flexural strength and flexural modulus of the samples were obtained on a tensile testing machine with an operating speed of 2 mm / min and a sample size of 80 × 10 × 4 mm. The impact strength was tested on a radial arm impact testing machine with a pendulum energy of 1 J, a sample size of 180 × 10 × 4 mm, and a hole depth of 2 mm.
[0043] 2. Experimental results
[0044] DTBP can be decomposed into oxygen free radicals and carbon free radicals at high temperature. These free radicals react with the double bonds of UHMWPE chains and TMPTMA to generate UHMWPE chain free radicals and TMPTMA free radicals. TMPTMA free radicals react with each other to form UHMWPE-UHMWPE networks and UHMWPE-TMPTMA-UHMWPE networks. Compared with the control shielding material 0phr DTBP without adding a crosslinking agent, the tensile strength, elongation at break and flexural strength of the DTBP crosslinked UHNMWPE shielding material of the present invention are significantly improved, and the flexural modulus and impact strength are slightly increased. Among them, the tensile strength and elongation at break of 0.2phr DTBP are increased by 48.90% and 154.68% respectively, and the flexural strength of 1.2phr DTBP is increased by 35.89% ( Figure 1 A and 1B).
[0045] The above experimental results show that the peroxide crosslinking method using DTBP and TMPTMA as crosslinking agent and crosslinking aid can improve the mechanical properties of crosslinked UHMWPE shielding materials at room temperature.
[0046] Experimental Example 2: Mechanical properties test of DTBP cross-linked UHMWPE shielding material at high temperature
[0047] 1. Experimental methods
[0048] The test method is consistent with that of Experimental Example 1. Before the test, the material is kept warm in a test box at the corresponding temperature for 1 hour.
[0049] 2. Experimental results
[0050] The results are as follows Figure 2As shown. The tensile strength, elongation at break, flexural strength and flexural modulus of the control shielding material 0phr DTBP without adding a crosslinking agent at 70°C are 4.21MPa, 2.53%, 7.75MPa, 619 respectively, and the tensile strength and flexural modulus at 90°C are 3.27MPa, 3.27%, 5.63MPa respectively. Compared with 0phr DTBP, the tensile strength, elongation at break, flexural strength and flexural modulus of the DTBP crosslinked UHNMWPE shielding material of the present invention at high temperature are significantly improved. Among them, the tensile strength and elongation at break of 0.2phr DTBP at 70°C are 8.65MPa (increased by 105.46%) and 6.35% (increased by 154.00%), respectively; the flexural strength of 1.2phr DTBP at 70°C is 13.28MPa (increased by 71.35%), and the flexural modulus of 0.8phr DTBP at 70°C is 728 (increased by 17.61%); the tensile strength and elongation at break of 0.8phr DTBP at 90°C are 7.48MPa (increased by 128.75%) and 6.00% (increased by 83.49%), respectively; the flexural strength and flexural modulus of 1.2phr DTBP at 90°C are 11.68MPa (increased by 107.46%) and 781 (increased by 67.96%), respectively.
[0051] The above experimental results show that the peroxide crosslinking method using DTBP and TMPTMA as crosslinking agent and crosslinking aid can improve the mechanical properties of crosslinked UHMWPE shielding materials at high temperatures.
[0052] Experimental Example 3: Test on the crosslinking degree and heat resistance of DTBP crosslinked UHMWPE shielding material
[0053] 1. Experimental methods
[0054] The Vicat softening point was collected on a heat deformation Vicat temperature tester at a heating rate of 120°C / h, and the sample was cut into 10×10×4mm. The heat deformation curve was carried out on a thermomechanical analyzer at a heating rate of 5°C / h, and the sample was cut into 10×10×4mm. The melting temperature was tested using a differential scanning calorimeter at a heating rate of 10°C / min.
[0055] 2. Experimental results
[0056] Table 2 Vicat softening temperature, maximum heat deformation temperature and melting temperature of UHMWPE shielding materials
[0057] Sample name Vicat softening temperature(℃) Maximum heat deformation temperature (℃) Melting temperature(℃) 0phr DTBP 120.8 118.34 134.59 0.2phr DTBP 124.1 118.79 133.05 0.5phr DTBP 124.8 120.84 132.90 0.8phr DTBP 125 124.9 131.96 1.2phr DTBP 124.1 125.32 132.52
[0058] from Figure 3It can be seen that with the addition of DTBP, the Vicat softening temperature and maximum heat deformation temperature of the material are generally increasing, and the melting point is generally decreasing. As shown in Table 2, when the DTBP content is 0.8phr, the Vicat softening temperature, maximum heat deformation temperature and melting temperature of the DTBP cross-linked UHMWPE shielding material are 125℃, 124.9℃ and 131.96℃ respectively, and the cross-linking degree can reach 27.51×10 -3 mol / g( Figure 3 ).
[0059] The above experimental results show that the peroxide crosslinking method using DTBP and TMPTMA as crosslinking agent and crosslinking aid can generate a crosslinked network, thereby improving the heat resistance of the crosslinked UHMWPE shielding material.
[0060] Experimental Example 4: Mechanical properties of DTBP cross-linked UHMWPE shielding material after irradiation with different doses of γ-rays
[0061] 1. Experimental methods
[0062] The gamma irradiation experiment used a BFT-IV Co-60 irradiator. The actual source loading was 1.6×106Ci, the radiation source activity was 6.29×1016Bq, and the dose rate was 0.75kGy / h. The total irradiation doses were 200, 400, and 600KGy, respectively. The mechanical properties test was consistent with the test at room temperature.
[0063] 2. Experimental results
[0064] Under low-dose γ-ray irradiation, the chains of UHMWPE are broken into chain radicals, which react with each other to form intermolecular bonds and form a cross-linked network. The control shielding material 0phrDTBP without adding a cross-linking agent forms a cross-linked network under 200KGy and 400KGy irradiation, and the tensile strength is enhanced ( Figure 4 and Figure 5 ). Under high-dose γ-ray irradiation, the polymer chains and cross-linked network structure formed by DTBP and γ-rays were decomposed, and the decomposition rate was greater than the reformation rate, resulting in a decrease in the tensile strength at 600KGy.
[0065] Since the cross-linked network formed by DTBP destroys the orderly accumulation of UHMWPE chains, the chain structure of the UHMWPE shielding material becomes a disordered structure. Compared with 0phr DTBP, the disordered chain structure in the DTBP cross-linked UHMWPE shielding material can generate a more complex cross-linked network after irradiation. At 600KGy, the tensile strength of 0phr DTBP is 16.59MPa, which is equivalent to the tensile strength of the unirradiated 0phrDTBP; at 600KGy, the tensile strength of the DTBP cross-linked UHMWPE shielding material 1.2phr DTBP is 26.54MPa, which is 5.06MPa higher than that of the unirradiated material ( Figure 6 ).
[0066] The above experimental results show that the peroxide crosslinking method using DTBP and TMPTMA as crosslinking agent and crosslinking aid can improve the mechanical properties of crosslinked UHMWPE shielding materials under high-dose γ-ray irradiation.
[0067] Experimental Example 5: Shielding performance of DTBP cross-linked UHMWPE shielding material against gamma rays and neutrons
[0068] 1. Experimental methods
[0069] The shielding performance of UHMWPE-based shielding materials was simulated and characterized using Geant4. The energy of the gamma ray was 1 MeV, the number of rays was 1 million, the energy of the neutron was 2 MeV, and the number of neutrons was 1 million.
[0070] 2. Experimental results
[0071] Geant4 is an open source toolkit for simulating particle penetration through materials. Its application areas include high energy, nuclear physics and accelerator physics, as well as medical and space science research. Geant4 can be used to conveniently characterize the gamma ray and neutron shielding performance of UNMWPE shielding materials.
[0072] When gamma-ray photons and neutrons pass through shielding materials, two situations occur: the original gamma-ray photons and neutrons disappear or change their energy after being scattered, and move away from the original direction. The other is that they pass through without changing. The attenuation of gamma-ray photons and neutrons in UHMWPE materials can be calculated by the following formula:
[0073] I=I0e (-μ·d)
[0074] Where, I is the penetration intensity through the UHMWPE shielding material; I0 is the incident intensity; μ is the linear attenuation coefficient; d is the thickness of the UHMWPE shielding material.
[0075] μ m =μ / ρ
[0076] In the formula, μm is the mass attenuation coefficient; ρ is the density of UHMWPE shielding material.
[0077] The shielding performance has a strong correlation with the element composition. The shielding material has good shielding performance. The Pb element and the H element react with gamma rays and neutrons respectively to reduce energy. The transmittance of 1Mev gamma rays and 2Mev neutrons with a thickness of 2mm are 58.88% and 58.01% respectively. UHMWPE shielding material can shield nearly half of the radiation with only 2mm thick UHMWPE shielding material. As the shielding thickness increases, the linear attenuation coefficient and mass attenuation coefficient decrease slightly ( Figure 7 ).
[0078] The above experimental results show that UHMWPE-based shielding materials have strong gamma-ray and neutron shielding properties.
[0079] In summary, the present invention provides a polyethylene-based heat-resistant shielding material and a preparation method thereof. The present invention improves the thermomechanical properties of polyethylene-based radiation shielding materials by cross-linking a high-hydrogen-containing polyethylene matrix, using ultra-high molecular weight polyethylene as a matrix, di-tert-butyl peroxide as a cross-linking agent, trimethylolpropane trimethacrylate as a cross-linking aid, and lead as a shielding filler, to develop a new multifunctional heat-resistant shielding material with gamma-ray shielding, neutron shielding, radiation resistance, and heat resistance, which has broad application prospects.
Claims
1. A heat-resistant shielding material, characterized in that: It is prepared from the following raw materials in parts by weight: 100 parts of high-density polyethylene, 0.1-3.0 parts of a cross-linking agent, 0.2-6.0 parts of a cross-linking aid, and 20-200 parts of a shielding filler. The high-density polyethylene is ultra-high molecular weight polyethylene, the cross-linking agent is di-tert-butyl peroxide, the cross-linking aid is trimethylolpropane trimethacrylate, and the shielding filler is lead.
2. The heat-resistant shielding material according to claim 1, characterized in that: The invention is prepared from the following raw materials in parts by weight: 100 parts of high-density polyethylene, 0.2-1.2 parts of a cross-linking agent, 0.4-2.4 parts of a cross-linking auxiliary agent and 80 parts of a shielding filler.
3. The heat-resistant shielding material according to claim 2, characterized in that: The invention is prepared from the following raw materials in parts by weight: 100 parts of high-density polyethylene, 0.8-1.2 parts of a cross-linking agent, 1.6-2.4 parts of a cross-linking auxiliary agent and 80 parts of a shielding filler.
4. A method for preparing the heat-resistant shielding material according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: plasticizing high-density polyethylene, adding shielding filler, crosslinking agent and crosslinking auxiliary agent, mixing evenly, and hot pressing to obtain heat-resistant shielding material.
5. The method according to claim 4, characterized in that: The plasticizing temperature is 150-170° C., and the time is 5-15 min; the hot pressing temperature is 200-220° C., the pressure is 5-15 MPa, and the time is 15-25 min.
6. Use of the heat-resistant shielding material according to any one of claims 1 to 3 in nuclear reactor devices, nuclear power plant operating devices, radioactive material transportation devices, radiation devices and medical and sanitary products thereof.
Citation Information
Patent Citations
Rotational molding grade cross-linked polyethylene wear-resistant composite and preparation method thereof
CN102492213A
Novel high-tungsten-content tungsten-boron cross-linked polyethylene composite shielding material
CN110767340A